THE INFLUENCE OF GENERIC SKILLS ON GENDER DIFFERENCES IN SCIENTIFIC PROCESSING AND CRITICAL THINKING IN PHYSICS MOTION DYNAMICS - Darmaji, Darmaji; Astalini, Astalini; Kamid, Kamid; Triani, Elza (LPPM Universitas Jambi, 2024)
This study investigates the gender differences in generic skills, scientific process abilities, and critical thinking among high school students during physics learning, specifically within motion dynamics. The research aims to uncover the impact of generic skills on students' scientific processing and critical thinking abilities while examining how gender influences these cognitive domains. Employing a comparative quantitative research design, data were gathered from 180 students (90 male and 90 female) in Jambi City using observation sheets, test questions, and questionnaires. The sample was selected through simple random sampling, and statistical analyses were performed to examine the differences in learning outcomes between genders. Results revealed notable gender disparities in generic skills, scientific processing, and critical thinking, with male and female students demonstrating distinct proficiencies in physics learning. This underscores the necessity of adopting gender-sensitive educational approaches to foster equitable learning experiences. The uniqueness of this research lies in its detailed exploration of the interconnectedness between generic skills, scientific processing, and critical thinking within the framework of gender. Unlike prior studies, which often focus on isolated skills, this study integrates these core competencies to provide a more holistic understanding of how gender influences physics learning. The findings emphasize the need for inclusive curricula and gender-tailored instructional strategies that promote equal opportunities for all students in science education, particularly in physics, thus contributing to a more balanced and equitable academic environment.